Personality functioning and mental distress in leaders of small- and medium sized enterprises. - Rebecca Erschens; Carla Schröpel; Sophia H Adam; Harald Gündel; Peter Angerer; Ulrike Dinger-Ehrenthal; Johannes C Ehrenthal; Mathias Diebig; Sophie Hofmann; Michael Gast; Susan Gritzka; Stephan Zipfel; et al. (PLoS ONE)
Objective For leaders of small and medium-sized enterprises (SMEs) grappling with diverse tasks and stressors, personality functioning can play a key role on stress perception and building and managing professional relationships. We investigated the relationship between SME leaders' personality functioning on the dimensions of self-perception and self-regulation on perceived stress reactivity (PSR), and symptoms of anxiety and depression. Methods A cross-sectional sub analysis of a multi-centre RCT project was performed. A sample of N = 174 SME leaders from various sectors in southern Germany were examined on their self-rated levels of personality functioning (OPD-SQ), involving self-perception (facets: self-reflection, affect differentiation, sense of identity) and self-reflection (facets: impulse control, affect tolerance, regulation of self-esteem), with higher scores indicating lower levels of personality functioning. The outcome variables were perceived stress reactivity (PSRS) and symptoms of depression and anxiety (HADS). Results The mean score for symptoms of anxiety was M = 6.13 (SD = 3.34), depression M = 4.40 (SD = 3.35), and for PSRS M = 21.39 (SD = 8.04). The mean sum score for self-perception was M = 7.71 (SD = 7.19) and for self-regulation M = 10.50 (SD = 7.09). The results of three regression models showed that higher scores for affect differentiation (rsp = .13), impulse control (rsp = .14) and regulation of self-esteem (rsp = .29) were associated with higher scores for PSR. Higher scores for affect differentiation (rsp = .17) and affect tolerance (rsp = .20) were significantly associated with higher scores for anxiety. A higher score for regulation of self-esteem (rsp = .17) was associated with higher depression scores. Conclusion This study highlights the association between core dimensions of SME leaders' personality functioning and mental distress. The findings can be applied on interventions and health promotion and the establishment of high-quality professional relationships and leadership skills.